Physiological and PIP Transcriptional Responses to Progressive Soil Water Deficit in Three Mulberry Cultivars - Cao, Xu; Shen, Qiudi; Ma, Sang; Liu, Li; Cheng, Jialing (Frontiers in Plant Science, 2020)
Although mulberry cultivars Wupu, Yu711 and 7307 display distinct anatomical and morphological characteristics under natural conditions, it remains unclear if they differ in drought tolerance. This study investigated the physiological responses and transcriptional changes of PIPs in saplings of these mulberry cultivars subjecting to progressive soil water deficit for 5 days. Cultivar Wupu displayed generally delayed stress responses comparing to the other two cultivars. Very slight changes of tissue water contents, PIPs transcript levels, concentrations of chlorophyll, superoxide anion, malonaldehyde (MDA) and free proline in leaves were observed on day 3 when stress level was mild. As drought stress intensified on day 5, Wubu sustained higher tissue water contents in green tissues, stronger responsiveness in PIPs transcription, lower starch concentration, lower MDA, higher free proline and soluble proteins, and higher activities of POD, APX, CAT. To confront gradual soil water depletion, all the mulberry cultivars exhibited differential expression of PIPs, decreased chlorophyll and starch, increased soluble sugars and free proline, and activation of antioxidant enzymes. Additionally, osmoregulatory substances and antioxidant enzymes in roots, wood, bark and leaves displayed significant responses to drought, whereas reactive oxygen species in wood and bark were less responsive. These data indicate that cultivar Wubu is more tolerant to drought than the other two cultivars to progressive drought and demonstrates that tissue-specific physiological and transcriptional response patterns at plant-level in acclimation to drought is important for mulberry to cope with and survive future drier climate scenarios.